Challenges of using tissue engineering methods in the treatment of hypospadias - Wilczek, P.; Bociaga, D.; Krakos, M.; Wierzbicka, A. (Frontiers in Bioengineering and Biotechnology, 2025)
Background and objectiveReconstructing the urinary tract in patients with hypospadias poses a significant clinical challenge. Despite numerous surgical approaches available, outcomes remain unsatisfactory due to the complexity of the condition and the lack of standardized conventional methods. Material requirements for reconstruction are stringent, necessitating resistance to fluids, adherence, and prevention of hair growth and strictures. Materials should also be biocompatible with the ability to control their biodegradation rate.MethodsA systemic search of PubMed database for studies between 2021 and 2024 was performed. The search terms included surgical methods hypospodia, stem cells in urethra reconstruction, polymer materials used in hypospodia, preclinical and clinical study in reconstruction of urinary system, tissue engineered methods used in urinary reconstruction.ResultsTreatment options are notably limited for patients requiring lengthy urethral fragments, primarily due to the scarcity of autologous tissue, particularly penile skin. There is still debate whether using a one- or two-stage surgical procedure is more appropriate. Regardless of the surgical technique used, the number of complications increases over time. It’s justify the search for new methods of urethral reconstruction Consequently, tissue engineering techniques, cell therapies, and advancements in biomaterials offer promising alternatives to traditional urinary tract reconstruction methods. However, it should be noted that at present, despite the promising results of in vitro studies, the translation of these studies into clinical practice is still unsatisfactory.Conclusion and clinical applicationWhile notable advancements have occurred in tissue engineering methods, cell therapies, and modern biomaterials in recent years, the translation of laboratory findings to preclinical and clinical applications remains inadequate. This deficiency primarily stems from the absence of standardization and the relatively short duration of clinical trial follow-ups.